Peritoneal Lipomatosis: A Case Report of a 12-Year-Old Boy - L. Fotis; J. Koglmeier; N. Shah (Case Reports in Gastrointestinal Medicine)
Peritoneal lipomatosis is a rare disease in childhood with only two cases previously described in children. We report a further case of a 12-year-old boy diagnosed with peritoneal lipomatosis. His main symptoms were abdominal pain, alternating bowel habit, abdominal distension, and melaena. His diagnostic work up included an abdominal MRI, wireless capsule endoscopy and single-balloon enteroscopy. Peritoneal lipomatosis although rare can be diagnosed in childhood. It is a benign clinical entity with variable manifestations.